Research support in a research assessment environment: The experience of 'new' universities - Haddow, Gaby (Library and Information Research Group, 2012)
The role of libraries in research support has attracted increasing notice in the past decade. This paper contributes another perspective on the topic by reporting on a study that used qualitative research methods to examine research support at six ‘new’ universities, all of which had significantly improved their ranked position after the 2008 Research Assessment Exercise. The study found that the influence of individuals and institution-wide initiatives are important in gaining a place in the discussions and activities surrounding research support, and a range of approaches to collection management are being implemented to maximize resources and information access. In the future, libraries will have to consider how best to develop expertise and skills in areas that add value to the services provided to researchers. They will also need to develop strategies for engaging and meeting the needs of new researchers.